PROFIL TITER ANTIBODI Avian Influenza (AI) dan Newcastle Disease (ND) PADA ITIK PEJANTAN DI KECAMATAN GADINGREJO KABUPATEN PRINGSEWU - Anggraini, Gabriella Ayu; Santosa, Purnama Edy; Suharyati, Sri (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
This study about profile of antibody titre in drake in Gadingrejo Subdistrict Pringsewu District hasbeen conducted in December – January 2014. The method used in this study were survey method andsample collecting by method of purposive random sampling. The data analysis used in this study wasdescriptive analysis. The variable observed was the antibody titreBased on the result of Hemaglutination Inhibition (HI) on Avian Influenza in drake in GadingrejoSubdistrict, there were 39% ducks that showed seropositive result on AI. There were 61% ducksshowed seronegative result on AI. Based on the result of HI test of Newcastle Disease in drake inGadingrejo Subdistrict Pringsewu District, there were 10% ducks that showed seropositive result and90% ducks with seronegative result on ND.